2013
DOI: 10.1176/appi.ps.201200315
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Distress After Seclusion or Mechanical Restraint: One-Year Follow-Up of a Randomized Controlled Study

Abstract: Contrary to the original study, the follow-up study suggested that seclusion might be a less restrictive alternative for most patients. The incidence of PTSD seemed lower than expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 20 publications
2
67
0
5
Order By: Relevance
“…() found that patients varied in their attitudes towards different types of coercive measures, but this present review, however, was unable to draw any overall conclusions about this. Some researchers argue that seclusion and MR, in particular, are often experienced as very intrusive and/or traumatic (Frueh et al., ; Bak & Aggernæs, ; Georgieva, Mulder, & Whittington, ; Steinert et al., ), and results from this review also indicate that these coercive measures were associated with “negative patient‐perceived impacts.” These findings should be treated with caution, however, due to the limited number of studies investigating patients’ perceptions of MR (see literature matrix Table ).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…() found that patients varied in their attitudes towards different types of coercive measures, but this present review, however, was unable to draw any overall conclusions about this. Some researchers argue that seclusion and MR, in particular, are often experienced as very intrusive and/or traumatic (Frueh et al., ; Bak & Aggernæs, ; Georgieva, Mulder, & Whittington, ; Steinert et al., ), and results from this review also indicate that these coercive measures were associated with “negative patient‐perceived impacts.” These findings should be treated with caution, however, due to the limited number of studies investigating patients’ perceptions of MR (see literature matrix Table ).…”
Section: Discussionmentioning
confidence: 61%
“…The mental health laws in most countries consider coercion to be acceptable in emergency situations to prevent harm to the patients themselves, other patients or staff (Albrecht, ). However, use is controversial, as the most recent Cochrane review shows no strong evidence of the value of seclusion and restraint (i.e., Sailas & Fenton, ), and serious physical and mental consequences from the use of coercive measures have been consistently reported (e.g., Tinetti, Liu, & Ginter, ; Evans, Wood, & Lambert, ; Mohr, Petti, & Mohr, ; Hui, Middleton, & Vollm, ; Steinert, Birk, Flammer, & Bergk, ). This had led to international calls to reduce the use of coercive measures in psychiatric/mental health settings and to improve clinical practice in this area (Bowers et al., ; Hui et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restrictive interventions are coercive, and cause consumers, carers, and clinicians to feel a range of negative emotions (Ashcraft & Anthony 2008;Bigwood & Crowe 2008;Larue et al 2013;Steinert et al 2013;Stubbs et al 2009). Restrictive interventions (seclusion, physical restraint, and mechanical restraint) might be authorized for consumers if they are considered to be an imminent and serious risk to themselves or another person (Wieman et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Haw et al 2011;Holmes et al 2015;Knowles et al 2015;Sequeira & Halstead 2002). The need for a distinct investigation into patients' perceptions of MR within the forensic setting is therefore required, as researchers argue that MR is one of the most intrusive types of containment methods (Bak & Aggernaes 2012), and Steinert et al (2013) found that patients' retrospective assessments of MR were significantly more negative than their assessments of seclusion.…”
Section: Introductionmentioning
confidence: 99%